Vegovi profesorji in njegova ocena pri matematiki - Južnič, Stanislav (Obzornik za matematiko in fiziko, 2014)
The newly discovered student Georg Vega's mark in mathematics is put in the limelight. In 1774 his teacher of mathematics was Josef Maffei, the assistant of Gabriel Gruber. The official troubles and reasons for Maffei and gruber's later departure from Ljubljana are discussed.
Keywords: zgodovina matematike; Jurij Vega; Gabrijel Gruber; Jožef Maffei